Agencification in Asia: Lessons from Thailand, Hong Kong, and Pakistan - Arif Budy Pratama (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2017)
This paper discusses the agencification phenomena as one of New Public Management (NPM)-based administrative reform initiatives. Thailand, Hong Kong, and Pakistan were chosen because of their similarity on administrative legacy and availability of data. The study uses a review of literature research method, while comparative approach was employed to analyze experiences of agencification in the three selected cases. Research result showed that the three countries implemented agencification in different ways; rational agency model is not the only driver for agencification initiatives; and contextual factor that include traditions, cultures, structures, and values influence the implementation of agencification process as a public sector reform initiative. Policy implications can be drawn by reading the three countries on agencification. Thus,  Indonesia, as one of NPM adopters can learn from experience gleaned from the three polities in conducting its administrative reform agenda.